The Effect of Nutritional Status and Contact History toward Childhood Tuberculosis in Jember - Anasyia Nurwitasari; Chatarina Umbul Wahyuni (Jurnal Berkala Epidemiologi, 2015)
Tuberculosis (TB) is one of the deadliest infectious diseases in the world. Since 2013 Indonesia has been categorized as a country with a high tuberculosis burden. Jember District in three years experienced an increase in the number of tuberculosis events. In 2014, 6.5% of the total TB cases in Jember District occurred in children. TB in children control is a major component in controlling TB incidence. The purpose of this study was to analyze the factors that influence the incidence of TB in children at Jember District. This study uses a case-control design with an analytic observational approach. Population of this research were children aged 0-14 who were diagnosed by Jember Lung Hospital suffering from TB. Samples were taken by simple random sampling method. The size of the case sample is 24 respondents and the control sample is 48 respondents. The independent variables of this study were the nutritional status of children, contact history, duration of contact, and closeness to patients with tuberculosis. Analysis of the influence between independent and dependent variables is performed using the Logistic Regression test. The results showed that the independent variables that had an influence on the incidence of pediatric tuberculosis were contact history (p = 0,000; OR = 26.6), contact duration (p = 0,000; OR = 69), and closeness (p = 0,000; OR = 27 , 1). In this study, it can be concluded that the contact history, duration of contact, and closeness influence the incidence of tuberculosis in children in Jember District. Actively searching for new cases was needed by checking household contacts as early as possible.